Premedication with intranasal dexmedetomidine decreases thiopental requirements in sedation of pediatric patients for magnetic resonance imaging: a retrospective study - Uusalo Panu; Lehtinen Mirjam; Löyttyniemi Eliisa; Manner Tuula; Scheinin Mika; Saari Teijo I. (My University, 2022)
Background
Barbiturates are commonly used in ambulatory sedation of pediatric patients. However, use of barbiturates involve risks of respiratory complications. Dexmedetomidine, a highly selective α2-adrenoceptor agonist, is increasingly used for pediatric sedation. Premedication with intranasal (IN) dexmedetomidine offers a non-invasive and efficient possibility to sedate pediatric patients undergoing magnetic resonance imaging (MRI). Our hypothesis was that dexmedetomidine would reduce barbiturate requirements in procedural sedation.
Methods
We included 200 consecutive pediatric patients undergoing MRI, and analyzed their hospital records retrospectively. Half of the patients received 3 μg/kg of IN dexmedetomidine (DEX group) 45–60 min before MRI while the rest received only thiopental (THIO group) for procedural sedation. Sedation was maintained with further intravenous thiopental dosing as needed. Thiopental consumption, heart rate (HR) and peripheral oxygen saturation were recorded.
Results
The cumulative thiopental requirement during MRI was (median and interquartile range [IQR]) 4.4 (2.7–6.0) mg/kg/h in the DEX group and 12.4 (9.8–14.8) mg/kg/h in the THIO group (difference 7.9 mg/kg/h, 95% CI 6.8–8.8, P <  0.001). Lowest measured peripheral oxygen saturation remained slightly higher in the DEX group compared to the THIO group (median nadirs and IQR: 97 (95–97) % and 96 (94–97) %, P <  0.001). Supplemental oxygen was delivered to 33% of the patients in the THIO group compared to 2% in the DEX group (P <  0.001). The lowest measured HR (mean and SD) was lower (78 (16) bpm) in the DEX group compared to the THIO group (92 (12) bpm) (P <  0.001).
Conclusion
Premedication with IN dexmedetomidine (3 μg/kg) was associated with markedly reduced thiopental dosage needed for efficient procedural sedation for pediatric MRI.